THE EFFECT OF USING CLUSTERING TECHNIQUE ON THE STUDENTS’ WRITING SKILLS IN DESCRIPTIVE TEXT AT SENIOR HIGH SCHOOL 10 MAKASSAR - Afika, Nurul; Kaharuddin; Abubakar, Multazam; Nawir, Muhammad Syahruddin (English Language, Linguistics, and Culture International Journal, 2022)
This research focuses on the students’ writing skills in writing descriptive text. The purpose of this research were (1) To find out if the clustering technique is able to improve the students skills in writing descriptive text. (2) To find out to what extent clustering technique affects the development of the students skills in writing descriptive text. In this research, the population was the First Grade of Senior High School 10 Makassar consist of 15 students from X IIS 1. The method of this study was a Mixed Method, the design of this study was The Explanatory-Sequential (QUAN-qual) design where quantitative data were collected first. Pre-experimental method was applied in this research with a group pre-test and post-test design. The instrument used to collect data were writing test and questionnaire. The result of the research presented that the pre-test of the class got the mean score 40.33. After giving treatment the students got the the mean score 71.00. The outcome of the data analysis revealed that there was a significant improvement in the students’ skill in writing descriptive text after being taught using clustering technique. It can also be supported the strength of clustering technique, that is the students can generate their ideas in writing descriptive text. Subsequently, the result of one sample t-test where Sig. (2-tailed) = 0,000 < 0.05. Therefore, the null (Ho) is rejected and the alternative hypothesis (H1) is accepted. In addition, the qualitative result from the questionnaire showed there were 4 factors affecting the development of students’ writing skill in descriptive text, those are: teaching materials’ content, method in the teaching process, activities in the teaching materials, task given in teaching materials. Based on the result analysis, the researcher may conclude that using Clustering Technique was effective to improve the students’ skill in writing descriptive text because the learning objective was achieved, that was the students were able to write English descriptive text appropriately in English by following the generic structure and language features.